Effectiveness of Structured Preconception Nutritional Counseling on Pregnancy Readiness Among Women Planning Pregnancy in Rural North Sumatra, Indonesia - Ika Damayanti Sipayung; Nurmalina Hutahaean; Yasrida Nadeak; Fazila Itawari; Juwita Pakpahan (Asosiasi Dosen Muda Indonesia, 2026)
Preconception nutritional readiness is an important component of maternal and neonatal health because women’s nutritional status before pregnancy may influence pregnancy outcomes, fetal growth, and newborn health. However, structured preconception nutritional counseling has not been widely implemented in rural community settings, including among women planning pregnancy in Bangun Rejo Village, North Sumatra, Indonesia. Objective: This study aimed to examine the effectiveness of structured preconception nutritional counseling on pregnancy readiness among women planning pregnancy. Methods: This study used a quantitative approach with a quasi-experimental non-equivalent control group design. A total of 80 women of reproductive age who intended to conceive within one year were selected using purposive sampling and divided into an intervention group and a control group, with 40 respondents in each group. The intervention group received structured preconception nutritional counseling for eight weeks, while the control group received routine health education. Data were collected using a pregnancy readiness questionnaire and analyzed using descriptive statistics, paired sample t-tests, and independent sample t-tests. Results: The results showed that the intervention group experienced a significant increase in pregnancy readiness scores from 61.75 ± 8.42 to 84.20 ± 6.11 after the counseling program (p < 0.001). In contrast, the control group showed only a small and statistically insignificant increase from 62.10 ± 7.95 to 65.45 ± 7.38 (p = 0.091). Improvements were also observed in nutritional knowledge, dietary behavior, and folic acid awareness, with the highest improvement found in folic acid awareness. Implications: These findings imply that structured preconception nutritional counseling can be integrated into community-based maternal and reproductive health services to improve women’s readiness before pregnancy. Originality: The originality of this study lies in its focus on structured nutritional counseling for women actively planning pregnancy in a rural Indonesian setting, providing practical evidence for strengthening preconception care at the community level.